A fatal case of Harlequin ichthyosis: Experience from low-resource setting - Vella, Vella; Maulida, Mimi; Earlia, Nanda; Hidayati, Arie; Handriani, Risna; Gondokaryono, Srie P.; Dwiyana, Reiva F.; Doris , Ezigbo E.; Pradistha , Aldilla; Bulqiah, Mikyal (Narra J, 2023)
Harlequin ichthyosis is a severe and fatal presentation of ichthyosis with an autosomal recessive inheritance. Infants with Harlequin ichthyosis have a high mortality rate, and a dismal prognosis; therefore the majority of neonates die shortly after birth from infection, heat loss, dehydration, electrolytic imbalances, or respiratory distress. The aim of this case report was to present a fatal case of Harlequin ichthyosis with no family history of any inherited skin disorder. A 3-day-old baby was presented to the emergency room with congenital abnormalities at birth, fissured hyperkeratotic skin, and thick yellow plates of scales. The parents had no history of consanguineous marriage, no relevant past medical history, and no family history of the same condition. The patient was unwell, pulse 162 times/minute, respiratory rate 48 times/minute, and axillary temperature 36.9oC. APGAR score was 8 in the 1st minute and 9 in the 5th minute. Based on the typical clinical appearance, the patient was diagnosed with Harlequin ichthyosis. Due to a lack of facility, a mutation analysis was not carried out. The patient was then transferred to the neonatal intensive care unit (NICU) and treated in a humidified incubator and medicated with intravenous antibiotics (ampicillin sulbactam 125 mg/12 hour and gentamicin 13 mg/24 hour), topically fusidic acid and mild emollients. A central venous catheter was used for intravenous access. The poor prognosis resulted in the patient dying at the age of 5-day-old. This case highlights that prenatal diagnosis is critical for early detection and disease prevention. Mutation screening for the ABCA12 gene is suggested for consanguinity marriages and with a history of ichthyosis.